A three-dimensional virtual morphometry study of the sigmoid notch of the distal radius - Shivdas, Sachin; Hashim, Muhammad Sufian; Ahmad, Tunku Sara (SAGE Publications (UK and US), 2018)
Purpose: Our primary objectives were to create a reliable, noninvasive method for three-dimensional morphometry of deep bony parameters within the sigmoid notch of the distal radius, to identify its morphological patterns, and to identify any significant variation between the left and the right wrists. Our secondary objectives were to obtain morphometric values that could represent our population and to identify any possible ethnic variations. Methods: Computed tomography scans of 102 wrists from 51 healthy individuals were analyzed using a virtualization software. Four anatomical parameters at the distal radius sigmoid notch, namely, the radius of curvature, depth, version angle, and sagittal slope were measured. Morphological patterns of the sigmoid notch surface were identified. The results were statistically analyzed to assess the reliability of the technique and were compared with previously published literature. Results: Comparing our findings with previously published values, our study revealed a slightly larger radius of curvature and sagittal slope, while revealing a smaller depth and version. We identified the S-type, C-type, and ski-slope morphological variants. The flat-face morphological variant, however, was not identified. The sigmoid notch at the left and right wrists were similar, except for the radius of curvature. Conclusion: This study demonstrates a noninvasive, fast, reliable, and reproducible technique for analyzing the sigmoid notch of the distal radius. In wrist injuries with intact distal radius sigmoid notch but involving comminuted fractures of the ulnar head, ulnar head replacement may be indicated. In such cases, analysis of the ipsilateral intact sigmoid notch would allow us to prepare an ulnar head prosthesis of appropriate size.